Scintigraphic Imaging of Neovascularization With 99mTc-3PRGD2 for Evaluating Early Response to Endostar Involved Therapies on Pancreatic Cancer Xenografts In Vivo - Jin, Xiaona; Dong, Chengyan; Zheng, Kun; Shi, Ximin; Liu, Yu; Huo, Li; Wang, Fan; Li, Fang (Frontiers in Oncology, 2021)
Background Molecular imaging targeting angiogenesis can specifically monitor the early therapeutic effect of antiangiogenesis therapy. We explore the predictive values of an integrin αvβ3-targeted tracer, 99mTc-PEG4-E[PEG4-c(RGDfK)]2 (99mTc-3PRGD2), for monitoring the efficacy of Endostar antiangiogenic therapy and chemotherapy in animal models. Methods The pancreatic cancer xenograft mice were randomly divided into four groups, with seven animals in each group and treated in different groups with 10 mg/kg/day of Endostar, 10 mg/kg/day of gemcitabine, 10 mg/kg/day of Endostar +10 mg/kg/day of gemcitabine at the same time, and the control group with 0.9% saline (0.1 ml/day). 99mTc-3PRGD2 scintigraphic imaging was carried out to monitor therapeutic effects. Microvessel density (MVD) was measured using immunohistochemical staining of the tumor tissues. The region of interest (ROI) of tumor (T) and contralateral corresponding site (NT) was delineated, and the ratio of radioactivity (T/NT) was calculated. Two-way repeated-measure analysis of variance (ANOVA) was used to assess differences between treatment groups. Results Tumor growth was significantly lower in treatment groups than that in the control group (p < 0.05), and the differences were noted on day 28 posttreatment. The differences of 99mTc-3PRGD2 uptakes were observed between the control group and Endostar group (p = 0.033) and the combined treatment group (p < 0.01) on day 7 posttreatment and on day 14 posttreatment between the control group and gemcitabine group (p < 0.01). The accumulation of 99mTc-3PRGD2 was significantly correlated with MVD (r = 0.998, p = 0.002). Conclusion With 99mTc-3PRGD2 scintigraphic imaging, the tumor response to antiangiogenic therapy, chemotherapy, and the combined treatment can be observed at an early stage of the treatments, much earlier than the tumor volume change. It provides new opportunities for developing individualized therapies and dose optimization.